ANALISIS KONDISI FISIK ATLET WUHSU KABUPATEN LIMAPULUH KOTA - Fauziati Tri Noviani; Hanif Badri (JURNAL STAMINA, 2019)
The problem in this study is that there is no training center on the physical condition of athletes and coaches have no data about the abilities of the athletes they develop. During training the trainer only focuses on training the components of the physical condition of endurance of the heart and lungs (cardiorespiratory) only. Whereas to support an athlete's achievement improvement, a coach should also know the quality of the components of other physical conditions such as strength, agility, explosive power, speed, and strength. This type of research is quantitative descriptive. The population in this study were Wuhsu athletes in Limapuluh Kota Regency, which numbered 15 male athletes. The sampling technique uses purposive sampling. Thus the sample in this study amounted to 15 male athletes. To obtain data tests and measurements were made on the abilities of the athlete's physical condition. Data were analyzed using descriptive analysis with percentages. The results of the study of physical conditions with tests and measurements showed that the physical condition of the largest percentage was as follows: (1) Muscle Power of Wushu athletes was 57.14% in the moderate category, (2) Stomach Strength of Wushu athletes was 71.43% in good category, ( 3) Muscle Strength of 78.57% Wushu athletes in the less category, (4) The speed of 50% Wushu athletes in the medium category, (5) The agility of 35.71% Wushu athletes in the medium category (6) Endurance Wushu athletes 64.29% in the moderate category.